A1 Beta-Casein Milk Transits the Stomach More Quickly Than A2 Beta-Casein Milk in Lactose Maldigesters Using Magnetic Resonance Imaging - Ramakrishnan, Monica; Dydak, Ulrike; Eaton, Tracy; Savaiano, Dennis; Zhou, Xiaopeng (Current developments in nutrition, 2022)
To compare the gastric transit time of milk containing A1 beta-casein and milk containing only A2 beta-casein in lactose maldigesters. We conducted a double-blinded, randomized, crossover trial. Subjects consumed each of the two types of milk: conventional New World milk containing 75% A1 beta-casein and 25% A2 beta-casein and Old World milk containing 100% A2 beta-casein, matched for macronutrient composition. Magnetic Resonance Imaging (MRI) images were acquired and symptoms were rated and recorded at 0, 10, 30, 60 and 120 minutes after consumption. Images were analyzed with FSL software and the volume of milk (ml) in stomach at 0, 10, 30, 60 and 120 minutes was calculated. The volume of milk in the stomach after consuming A1 milk was significantly lower at 10 (P = 0.04), 30 (P = 0.07), 60 (P = 0.04) and 120 (P = 0.001) minutes as compared to A2 milk (N = 6), demonstrating more rapid transit. There is more rapid transit after consumption of New World milk containing A1 beta-casein. This difference in transit may mediate symptoms of lactose intolerance. Gift funds from A2 milk company.